Income shocks, political support and voting behaviour - Richard Upward; Peter Wright (Halle Institute for Economic Research (IWH), 2024)
We provide new evidence on the effects of economic shocks on political support, voting behaviour and political opinions over the last 25 years. We exploit a sudden, large and long-lasting shock in the form of job loss and trace out its impact on individual political outcomes for up to 10 years after the event. The availability of detailed information on households before and after the job loss event allows us to reweight a comparison group to closely mimic the job losers in terms of their observable characteristics, pre-existing political support and voting behaviour. We find consistent, long-lasting but quantitatively small effects on support and votes for the incumbent party, and short-lived effects on political engagement. We find limited impact on the support for fringe or populist parties. In the context of Brexit, opposition to the EU was much higher amongst those who lost their jobs, but this was largely due to pre-existing differences which were not exacerbated by the job loss event itself.
urn:nbn:de:gbv:3:2-1029929
Keywords: C21; C23; D72; J63; 330; job loss; political support; voting